Evolving Immuno-Chemotherapeutic Paradigms in Esophageal and Gastric Cancers - Alexander Siebenhuener (healthbook TIMES. Oncology Hematology)
Esophageal (EC) and gastric (GC) cancers represent severe global health issues. Within the last 18 months, the standard of care has significantly evolved for the first-line setting of advanced EC and GC within the field of human epidermal growth factor receptor 2 (HER2)-negative and HER2-positive patients. The breakthrough concepts for clinical practice of immune checkpoint inhibitors (ICIs) plus chemotherapy in both fields were presented at major oncology meetings over the last 2 years. This review summarizes the latest results on when and how to use the new combinations and highlights the unsolved issues in this new era.